Strategi Penerapan Manajemen Risiko Cedera Tekan oleh Perawat - Reni Dwi Rusnawati; Rr. Tutik Sri Hariyati; Lilis Rayatin; Ahsan Ahsan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify risk management for pressure injuries, determine strategies for controlling and preventing pressure injuries, and evaluate prototype tools. The method used is a case study with an Analysis, Design, Development, Implementation, and Evaluation (ADDIE) approach. The results showed that 90% of nurses said the work instructions and the patient repositioning aid prototype tested were easy to use. In conclusion, fulfilling the need for pressure injury prevention equipment is one of the strategies for implementing risk management, namely preparing facilities and infrastructure, including infrastructure and standard operating procedures. The author recommends evaluating with a larger sample to develop a validated tool. Keywords: Patient Repositioning Tool, Pressure Injury, Risk Management